The art of shampoos in canine and feline dermatology: Treatment and prevention strategies - CARLOTTI, D. N.; GATTO, H. (Journal of the Hellenic Veterinary Medical Society, 2017)
This paper reviews the current technology pertaining to veterinary shampoos used for dogs and cats. The criteria used to evaluate their efficacy are presented. The indications for the use of shampoos in keratoseborrhoeic disorders, parasitic diseases, bacterial diseases, fungal diseases and allergic diseases are reviewed. In keratoseborrhoeic disorders both keratomodulating and antiseborrhoeic agents are used. Antiparasitic shampoos are not frequendy used in veterinary dermatology and their indications and limitations are discussed. Antibacterial, antifungal and antiseptic agents are included in shampoos designed to treat dermatoses resulting from microbiological agents. Their indications and efficacy are presented. Shampoos are used nowadays in conjunction with other forms of therapy to treat allergic skin diseases. The benefits of such adjunctive topical therapy are discussed. Lastly, the properties of moisturizers are presented and the value of their use in combination with therapeutic shampoos is emphasized.